A clinical practice guideline for the screening and assessment of enthesitis in patients with spondyloarthritis - Wu, Xinyu; Liu, Dong; Li, Yanfei; Xie, Ya; Tu, Liudan; Zhang, Yanli; Zhang, Xi; Fang, Linkai; Luo, Xiqing; Lin, Zhiming; Liao, Zetao; Rong, Limin; et al. (Frontiers in Immunology, 2022)
Objective The aim of this review is to provide guidance on the selection of approaches to the screening and assessment of enthesitis in patients with spondyloarthritis (SpA). Methods Twenty-four questions regarding the approaches to the screening and assessment of enthesitis and the implementation details were devised, followed by a systemic literature review. The Grading of Recommendations Assessment, Development, and Evaluation methodology was employed in the development of this guideline, with modifications to evaluate non-interventional approaches under comprehensive consideration of costs, accessibility, and evidence strength. A consensus from the voting panel was required for the inclusion of the final recommendations and the strength of each recommendation. Results Seventeen recommendations (including five strong recommendations) were included in this guideline. The voting panel expressed unequivocal support for the necessity of screening and assessment of enthesitis in patients with SpA. It was agreed unanimously that symptom evaluation and physical examination should serve as the initial steps to the recognition of enthesitis, whereas Maastricht Ankylosing Spondylitis Enthesitis Score is a reliable tool in both clinical trials and daily medical practice. Ultrasound examination is another reliable tool, with power Doppler ultrasound as an informative addition. Notwithstanding its high resolution, MRI is limited by the costs and relatively low accessibility, whereas radiographs had low sensitivity and therefore should be rendered obsolete in the assessment of enthesitis. PET/CT was strongly opposed in the detection of enthesitis. Conclusion This guideline provides clinicians with information regarding the screening and assessment of enthesitis in patients with SpA. However, this guideline does not intend on dictating choices, and the ultimate decisions should be made in light of the actual circumstances of the facilities.